Pancreatic Resection for Metastasis to the Pancreas from Colon and Lung Cancer, and Osteosarcoma - Lasithiotakis, Konstantinos; Petrakis, Ioannis; Georgiadis, George; Paraskakis, Stefanos; Chalkiadakis, George; Chrysos, Emmanuel (JOP. Journal of the Pancreas, 2010)
Context Pancreatic resection for a metastatic colon, lung cancer or an osteosarcoma has rarely been reported in the literature and there is controversy regarding recurrence and the overall survival of these patients. We herein evaluate the outcome of three patients who underwent pancreaticoduodenectomy for the aforementioned metastatic tumors to the pancreas. Case reports Clinical presentation included pyloric stenosis and acute gastrointestinal bleeding. One patient was asymptomatic and was diagnosed during follow-up for colon cancer. All the pancreatic lesions were located in the head of the pancreas, and the intervals between the diagnosis of the primary cancer and the pancreatic metastases were 6, 14 and 24 months. During exploration of the abdomen, additional metastatic lesions in the small intestine and liver were detected and resected in two patients. One patient died one month after surgery from massive gastrointestinal bleeding. The other two patients experienced relief from their symptoms but died from generalized carcinomatosis 16 and 27 months after pancreaticoduodenectomy. Conclusion Pancreatic resection for metastatic disease may be suggested for selected patients, even those with limited extrapancreatic disease. In this setting, it may offer good palliation and may prolong survival. In cases of acute duodenal bleeding resistant to conservative measures, pancreaticoduodenectomy may represent the only alternative for survival; however, significant morbidity and mortality should be expected. Image: Metastatic lesion to the head of pancreas from osteosarcoma.